Izkoriščenost topoklimatskega vinogradniškega potenciala v Slovenskih goricah - Žiberna, Igor (Časopis za zgodovino in narodopisje, 2025)
The article examines the topoclimatic potential of the Slovenske gorice region and changes in its utilization in the period 2000–2025. Topoclimatic viticultural potential combines relief characteristics, relative elevation, slope, and slope aspect, together with the associated solar radiation. All of these factors influence local climatic conditions, among which relief is one of the most important modifiers. Grapevine is a crop that, at our geographical latitudes, is highly dependent on topoclimatic characteristics and is better suited to warmer and more sun-exposed areas. The article first provides a typification of the Slovenske gorice from the perspective of topoclimatic characteristics, and then analyzes actual land use in the highest-quality topoclimatic areas for grapevine cultivation. It also examines changes in land use and the directions of land-use change in these areas in the period 2000–2025.
Keywords: land use; raba tal; Slovenske gorice; topoclimate; topoklima; vinogradništvo; viticulture